Uncovering the mechanism of Qidan Dihuang Granule in the treatment of diabetic kidney disease combined network pharmacology, UHPLC-MS/MS with experimental validation - Lei Xiang; Xiangsheng Cai; Xiaoshan Zhao; Yuanling Liu; Ya Xiao; Pingping Jiang; Lianghong Yin; Dan Song; Xuefeng Jiang (Heliyon, 2023)
Background and aim: Diabetic Kidney Disease (DKD) is a common microvascular complication of diabetes mellitus. Multi-center, randomized controlled trials have shown that Qidan Dihuang Granule (QDDHG) reduces the levels of albuminuria of DKD. However, the specific mechanisms of QDDHG on DKD are not clarified. Thus, this study utilized network pharmacology, UHPLC-MS/MS (Ultra-High Performance Liquid Chromatography - Mass Spectrometry) and animal experiments to reveal the mechanisms of QDDHG on DKD. Experimental procedure: Screening and retrieving active ingredients and corresponding targets of QDDHG on DKD through the TCMSP, ETCM, Disgenet, GeneCards, Omim and DrugBank databases. The PPI were performed with BioGrid, STRING, OmniPath, InWeb-IM. AutoDock Vina molecular docking module to estimate the validation from the compounds and target proteins. Free energy to estimate the binding affinity for identified compounds and target proteins. The ingredients of QDDHG were analyzed utilizing UHPLC-MS/MS. In vivo experiment with db/db mice were used to verify the targets and pathway predicted by network pharmacology. Results and conclusion: The results demonstrated that QDDHG has 18 active compounds and 13 target proteins of QDDHG exerted a crucial role in treatment of DKD. QDDHG affect the multiple biological processes included cellular response to lipid, response to oxidative stress, and various pathways, such as AGE-RAGE, PI3K-Akt, MAPK, TNF, EGFR, STAT3. The results of UHPLC-MS/MS showed that six ingredients predicted by network pharmacology were also verified in experiment. In vivo experiment verified the effects of QDDHG on protecting the renal function mainly through inhibited the expression of EGFR, STAT3 and pERK in the db/db mice.